Drug utilization study in patients visiting dermatology outpatient department in tertiary care hospital - Rizvi, Salman H.; Gawali, Ujwala P.; Mishra, Prashant S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: With the surge of basic and clinical research activities, and subsequent recognition of newer dermatological disorders; dermatology is now considered to be one of the most important specialties in a healthcare setup. Dermatological problem in India manifests as primary and secondary cutaneous complaints. The aim of this study was to assess current prescribing practices among physicians for dermatology patients in tertiary care hospital. Methods: A prospective, observational and cross-sectional study was conducted in Department of Pharmacology in collaboration with Department of Dermatology in a tertiary healthcare hospital. As per inclusion criteria, patients visiting Dermatology Outpatient department (OPD) from October 2018 to December 2018 were enrolled in the study. Results: The average number of drugs per encounter was 4.9. 100% of the drugs were prescribed by their generic name and those prescribed from World Health Organization (WHO) list of essential medicines were 68.9%. Analysis of polypharmacy showed maximum 11 and minimum 2 drug was prescribed. Overall analysis of the drugs showed, the most common route of administration was orally. Antihistamines, antifungals and steroids constitute the major bulk of drug prescribed. Conclusions: In our study, though polypharmacy was found but it was necessary as per the conditions. Anti-fungal, antihistamines and steroids were the most common drugs prescribed. Prescriptions with injections and steroids were less in the study population. All the drugs were prescribed by their generic name and most were present in the essential list of medicines. Use of Nonsteroidal anti-inflammatory drugs (NSAIDs) was higher in our study as compared to other studies.